Pengaruh Limbah Serbuk Kayu Mahoni Sebagai Subtitusi Agregat Halus Sebagai Campuran Beton - Tria Mahyuni Palian; Frans Phengkarsa; Luciana Buarlele (Paulus Civil Engineering Journal, 2023)
Sawdust is a waste from sawing wood which is often found in furniture manufacturing places such as doors, windows, frames, cabinets, and others. Often the waste from sawdust causes problems in its use which has a negative impact on the environment. In this study, mahogany sawdust was used as an additive in the concrete mixture, where mahogany sawdust was relatively cheap and easy to obtain. The purpose of this study was to determine the effect of variations of mahogany wood powder with mahogany wood powder added as a concrete mixture by testing compressive strength, split tensile, and flexural strength with design concrete quality 20 MPa. The research was conducted at the Structure and Materials Laboratory, Department of Civil Engineering. The type of research carried out is experimental using the SNI method. Based on the results of tests that have been carried out in cylinder and beam specimens on several variations of mahogany sawdust 0%, 4%, 8% and 12%, the compressive strength values ​​are 20,216 MPa, respectively. 19.750 MPa, 19.074 MPa and 18.111 MPa, the split tensile strength values ​​are 2.287 MPa, 2.004 MPa, 1.768 MPa and 1.509 MPa for flexural strength, the values ​​are 2.645 MPa, 2.491 MPa, 2.157 MPa and 1.720 MPa. From the results of the study the use of mahogany sawdust as a concrete mixture can affect the strength of concrete, where the strength of the concrete decreases based on the added variation, the higher the variation of mahogany sawdust is added, the strength of the concrete will decrease.